Lazer, aventura e risco: reflexões sobre atividades realizadas na natureza - Marinho, Alcyane [UNESP] (Universidade Federal do Rio Grande do Sul (UFRGS), Escola de Educação Física, 2008)
This paper reflects on the conceptions of adventure and risk, revealed in activities in nature. The presented speeches are contained in a research, whose boarding works with a universe of reasons, aspirations, values, beliefs and attitudes, corresponding to a deeper space of the processes, relations and phenomena. It was possible to perceive that the adventure activities in nature are carrying of innumerable meanings, related with new discoveries, new challenges, search for the stranger, uncertainty, cooperation, friendship, among others. Such activities understand diverse forms of experimentation, pointing besides to physical risk, the symbolic and imaginary risk.
Leisure, Adventure and Risk: reflections about activities in nature
Keywords: Leisure activities; Adventure; Risk; Nature